2017
DOI: 10.1016/j.pmrj.2017.08.403
|View full text |Cite
|
Sign up to set email alerts
|

A Focused Review of Safety Considerations in Cancer Rehabilitation

Abstract: Cancer and its treatments introduce various adverse effects that may impact survivors’ physical, cognitive and psychological functioning. Frequently both tolerance to activity and exercise are affected as well. Rehabilitation providers should have substantive knowledge about the effect of cancer progression and common side effects associated with anti-neoplastic treatment to safely integrate rehabilitation interventions. Rehabilitation may mitigate loss of function and disability; however, these patients are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
117
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(121 citation statements)
references
References 110 publications
1
117
0
2
Order By: Relevance
“…Session compliance was monitored during weekly phone calls which were in addition to collecting information to help progress the NMES prescription, were used to maximise the compliance with the intervention, encourage continued increase in stimulation intensity where possible, and to identify and solve problems. In addition, due to the cognitive issues which can be experienced by individuals undergoing treatment such as memory loss 32 written instruction manuals were provided with NMES units.…”
Section: Physiological and Subjective Responses To Lf-nmes Incrementmentioning
confidence: 99%
“…Session compliance was monitored during weekly phone calls which were in addition to collecting information to help progress the NMES prescription, were used to maximise the compliance with the intervention, encourage continued increase in stimulation intensity where possible, and to identify and solve problems. In addition, due to the cognitive issues which can be experienced by individuals undergoing treatment such as memory loss 32 written instruction manuals were provided with NMES units.…”
Section: Physiological and Subjective Responses To Lf-nmes Incrementmentioning
confidence: 99%
“…In 2015, a group of physiatrists from a variety of institutions across the US developed a modern definition for cancer rehabilitation aimed at clarifying some of the confusion: “Cancer rehabilitation is medical care that should be integrated throughout the oncology care continuum and delivered by trained rehabilitation professionals who have it within their scope of practice to diagnose and treat patients' physical, psychological and cognitive impairments in an effort to maintain or restore function, reduce symptom burden, maximize independence and improve quality of life in this medically complex population” [31]. Cancer rehabilitation physiatrists and other rehabilitation specialists have continued to educate colleagues about the role of the physiatrist [32], safety concerns in these complicated patients [33,34], and employment and disability issues in these patients [35,36].…”
Section: The Rise Of Survivorship Carementioning
confidence: 99%
“…Both physical and psychological impairments contribute to decreased quality of life which may result in disability. Recently, many researchers have demonstrated that cancer rehabilitation improves physical impairments at every stage along the treatment course for a variety of cancer types [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%